2022
DOI: 10.1001/jamadermatol.2021.4812
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy Positivity in Patients With Acral Lentiginous and Other Subtypes of Cutaneous Melanoma

Abstract: IMPORTANCE Acral lentiginous melanoma (ALM) is a rare subtype of malignant melanoma typically occurring on the palmar and plantar surfaces. Although it has distinctive genetic, prognostic, and behavioral characteristics relative to cutaneous melanomas overall, owing to its rarity, treatment is largely guided by data extrapolated from more common subtypes. Although sentinel lymph node (SLN) status has been shown to be a significant prognostic factor for ALM, the independent effect of ALM-subtype disease on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…This distant metastasis characteristic of AM is often one of the important factors for poor prognosis of patients. [21] The prognosis of AM also depends on a variety of other factors, including region, race, gender, age, etc, [1] as well as the stage of cancer at the time of diagnosis, [1] Breslow thickness, [22] combined ulcers, [23] pathological stage, [24] and sentinel lymph node positive [25] and the overall health status of the individual. Studies have shown that, [26] sentinel lymph node positive is the strongest predictor of melanoma disease recurrence and death.…”
Section: Discussionmentioning
confidence: 99%
“…This distant metastasis characteristic of AM is often one of the important factors for poor prognosis of patients. [21] The prognosis of AM also depends on a variety of other factors, including region, race, gender, age, etc, [1] as well as the stage of cancer at the time of diagnosis, [1] Breslow thickness, [22] combined ulcers, [23] pathological stage, [24] and sentinel lymph node positive [25] and the overall health status of the individual. Studies have shown that, [26] sentinel lymph node positive is the strongest predictor of melanoma disease recurrence and death.…”
Section: Discussionmentioning
confidence: 99%
“…7 The risk for a positive sentinel node may also be higher for some specialty site melanomas; although data are minimal for vulvar melanomas, recent work has demonstrated very high rates of positive sentinel nodes in patients with acral melanoma. 50 With patients who have regional disease becoming eligible for potentially lifesaving adjuvant immunotherapy, this is an important part of an adequate staging workup based on a tumor's T stage. [51][52][53][54] MMS is typically an in-office procedure and SLNB is typically performed in the operating room concurrently with excision of the primary tumor, as was performed in 84.3% of cases in our analysis, the logistical coordination of SLNB before MMS is a potential limitation to the use of MMS for vulvar melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of SLN metastases may differ among subtypes of melanoma. In a retrospective study comparing the rate of positive SLNB results among subtypes of melanoma (SSM, LMM, ALM, NM, and others), ALM was independently associated with the highest risk for positive SLNB results, whereas LMM was associated with the lowest risk among the included subtypes [ 44 ]. A subgroup analysis demonstrated that ALM was also independently associated with the highest risk for positivity of SLNB results in both stage IB and stage II disease [ 44 ].…”
Section: Role Of Slnb In Skin Cancermentioning
confidence: 99%
“…In a retrospective study comparing the rate of positive SLNB results among subtypes of melanoma (SSM, LMM, ALM, NM, and others), ALM was independently associated with the highest risk for positive SLNB results, whereas LMM was associated with the lowest risk among the included subtypes [ 44 ]. A subgroup analysis demonstrated that ALM was also independently associated with the highest risk for positivity of SLNB results in both stage IB and stage II disease [ 44 ]. These results suggest that SLNB should be more encouraged for patients with ALM than for those with the other subtypes, especially in cases of stage IB or stage II disease.…”
Section: Role Of Slnb In Skin Cancermentioning
confidence: 99%